Phytochemical and biological evaluation of some Sargassum species from Persian Gulf - Negin Mehdinezhad; Alireza Ghannadi; Afsaneh Yegdaneh (Wolters Kluwer Medknow Publications, 2016)
Sea algae are widely consumed in the world. There are several seaweeds including brown algae which are authorized for human consumption. These plants contain important phytochemical constituents and have various potential biological activities. The present study investigated the presence of phytochemical constituents and total phenolic quantity of the seaweeds Sargassum angustifolium, Sargassum oligocystum and Sargassum boveanum. Cytotoxicity of seaweeds was tested against HT-29, HeLa and MCF-7 cell lines. Antioxidant potential of these 3 Sargassum species was also analyzed. Cytotoxicity was characterized by IC50 of human cancer cell lines using sulforhodamine assay. Antioxidant activities were evaluated using 2,2-diphenyl-1- picrylhydrazil. The analysis revealed that tannins, saponins, sterols and triterpenes were the most abundant compounds in these Sargassum species while cyanogenic and cardiac glycosides were the least ones. Sargassum angustifolium had the highest content of total phenolics (0.061 mg/g) and showed the highest antioxidant activity (IC50 = 0.231). Cytotoxic results showed that all species could inhibit cell growth effectively, especially MCF-7 cell line (IC50 = 67.3, 56.9, 60.4 for S. oligocystum, S. angustifolium and S. boveanum respectively). Considerable phytochemicals and moderate cytotoxic activity of S. angustifolium, S. oligocystum and S. boveanum make them appropriate candidate for further studies and identification of their bioactive principles.